Melihat Latar Belakang Australia Dalam Memberikan Bantuan Luar Negeri ke Kawasan Pasifik - Yusuf Rifaldy (Jurnal Hubungan Internasional, 2020)
Australia is one of the largest foreign assistance donor country to thecountries in the Pacific Region. Besides the proximity of geographiclocation between the two, there are various other factors that causeAustralia to provide foreign assistance to the Pacific Region. The Pacificregion which consists of small countries and mostly an island nation with alow economic level has a high dependence on foreign aid provided by othercountries. This study was conducted to look at Australia’s background inproviding foreign assistance to countries in the Pacific Region and whatwas generated and achieved from the provision of foreign assistance. Thisstudy uses literature-based data collection, both using official documentsissued by parties related to Australia’s foreign aid issues and otherrelated documents. The results obtained from this study are that Australiaprovides foreign assistance to countries in the Pacific Region that cannotbe separated from Australia’s efforts to obtain its national interests, bothin terms of security, economy, and politics.